Essential role of ABA signaling and related transcription factors in phenolic acid and lignin synthesis during muskmelon wound healing - Wang, Qihui; Liu, Ning; Yang, Ruirui; Zhang, Xuejiao; Wang, Ying; Li, Yongcai; Prusky, Dov; Bi, Yang; Han, Ye (Frontiers in Plant Science, 2024)
Abscisic acid (ABA) is a key phytohormone involved in wound healing in fruits and vegetables, and fluridone (FLD) is its synthesis inhibitor. However, it is unknown whether ABA signaling and downstream transcription factors are involved in the synthesis of phenolic acids and lignin monomers in muskmelon wounds and what the underlying mechanisms are. In our research, exogenous ABA promoted endogenous ABA synthesis by increasing the levels of β-carotenoid and zeaxanthin, activating 9-cis-epoxycarotenoid dioxygenase (NCED) and zeaxanthin epoxidase (ZEP), facilitated ABA signaling by increasing the expression levels of protein phosphatases type 2C (CmPP2C) and ABA-responsive element binding factors (CmABF), upregulated the expression levels of CmMYB1 and CmWRKY1, and ABA induced phenylpropanoid metabolism by activating phenylalanine ammonia-lyase (PAL), 4-coenzyme A ligase (4CL), and cinnamyl alcohol dehydrogenase (CAD), which further increased the synthesis of phenolic acid and lignin monomer in muskmelon wounds during healing. Taken together, exogenous ABA induced phenylpropanoid metabolism and increased the synthesis of phenolic acid and lignin monomer in muskmelon wounds during healing, and may be involved in endogenous ABA synthesis and signaling and related transcription factors.